2015
DOI: 10.7325/galemys.2015.a1
|View full text |Cite
|
Sign up to set email alerts
|

Roosting behaviour and phenology of the Lesser horseshoe bat (Rhinolophus hipposideros) in a breeding colony in Sintra, Portugal

Abstract: Almost all bats are exclusively nocturnal. However, the activity patterns throughout the night can differ between species and also within the same species from place to place. Rhinolophus hipposideros (Bechstein, 1800) has suffered a severe decline in many countries along its distribution area, including Portugal. In this study we aimed to describe the roosting behaviour during spring, summer and autumn of one of the largest maternity colonies of R. hipposideros known in Portugal. We analysed roost occupancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…However, all nurseries provided secured entrances which may constitute a crucial factor for the survival of the non-fledged juveniles left behind in the nursery during the night. Across nurseries, higher temperatures correlated with an earlier onset of parturition, confirming previous findings in various geographic regions (e.g., Schofield 1996;Zahn 1999;Lino et al 2015). Moreover, we found a higher proportion of reproductive females in warmer nurseries.…”
Section: Roosting Ecology Of Nurseriessupporting
confidence: 91%
See 2 more Smart Citations
“…However, all nurseries provided secured entrances which may constitute a crucial factor for the survival of the non-fledged juveniles left behind in the nursery during the night. Across nurseries, higher temperatures correlated with an earlier onset of parturition, confirming previous findings in various geographic regions (e.g., Schofield 1996;Zahn 1999;Lino et al 2015). Moreover, we found a higher proportion of reproductive females in warmer nurseries.…”
Section: Roosting Ecology Of Nurseriessupporting
confidence: 91%
“…Thus, in the present study, roost switching was either conducted by males, which have a higher affinity to change roosts (compare Downs et al 2016), or by non-reproductive females. In contrast, studies from Central Europe showed roost switching of females with their pups, caused by changes in temperatures that where either too low (Kolb 1950;Lino et al 2015) or too high (Kayikcioglu and Zahn 2004). This discrepancy may be accounted for by two facts: in our study, the temperature of 34°C given in Kayikcioglu and Zahn (2004) was never exceeded in all parts of a given nursery so that bats could move to alternative perching sites (compare e.g.…”
Section: Roosting Ecology Of Nurseriescontrasting
confidence: 76%
See 1 more Smart Citation
“…Recent advances in technology have enabled scientists to address important questions about the social life and phenology of bats (Sedgeley 2012a, Rydell & Russo 2015, Lino et al 2015. Remote camera traps are a non-invasive method that can outperform traditional methods of visual counts and provide valuable information on the social behavior, phenology, daily movements and activity cycle of bats (Sedgeley 2012b, Lino et al 2015). The present paper provides data about a non-intrusive and novel method to monitor bat populations using time lapse cameras (Rydell & Russo 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The first juveniles appeared in the small and hotter room, indicating that temperature might play an important role in the timing of reproduction (Lucan et al 2013). This species positively selects warm roosts during the lactation period (Schofield 1996, Lino et al 2015, which may be the reason why they first gave birth in the small room. Later, during the season when temperatures were similar between the two rooms, females also gave birth in the larger room.…”
Section: Discussionmentioning
confidence: 99%